Left Isomerism With Normal Bronchopulmonary Anatomy: Broadening the Heterotaxy Spectrum - Zach Sukin; Erin Moffett; Madison Wulfeck; Dennis Lindfors; Sandor Szilagyi (Case Reports in Radiology)
Situs ambiguous is a rare congenital condition characterized by the abnormal arrangement of thoracoabdominal organs along the left–right axis. This condition often presents as either left or right isomerism, leading to complex anatomical variations and associated clinical challenges. We present the case of a 44-year-old female who was incidentally discovered to have situs ambiguous with polysplenia and left atrial appendage isomerism during the evaluation of abdominal pain and urinary symptoms caused by a ureteral calculus. Notably, the patient exhibited normal bronchopulmonary anatomy. The patient underwent a ureteroscopy, laser lithotripsy, stone extraction, and right ureteral stent placement. The patient was discharged shortly thereafter. We believe our case underscores the critical importance of recognizing the potential dissociation between thoracic and abdominal isomerism. It also highlights the need for further investigation into the embryological processes that contribute to these unusual presentations.